Changes in the Learning Behavior of the Islamic University Students during the Covid-19 Pandemic - Yusnaini Yusnaini; Dinn Wahyudin; Rusman Rusman (AL-ISHLAH: Jurnal Pendidikan, 2023)
Online learning is different from offline learning, and the various academic atmosphere, facilities, and infrastructure cause changes in behaviour. By comparing how students learn in the face-to-face learning process to how they learn when using the internet, this study hopes to find and explain the factors that change how students learn when using the internet. This study uses descriptive and quantitative methods, and 99 students at an Islamic university in Lhokseumawe were asked to participate. The results showed that: (1) all indicators of learning behaviour in learning using the internet network decreased in percentage compared to face-to-face learning, but this percentage decrease was still within the range of reasonable interpretation; and (2) every item in the questionnaire showed that there is a change in learning using the internet network, with more answer choices sometimes and less answer choices often or always. This is a sign that learning to use the internet for too long will cause students to change the way they learn in a wrong way or not the way they should.